Caffeic acid phenethyl ester: A review on its pharmacological importance, and its association with free radicals, COVID‐19, and radiotherapy. (23rd December 2022) - Taysi, Seyithan; Algburi, Firas Shawqi; Taysi, Muhammed Enes; Caglayan, Cuneyt
Abstract: Caffeic acid phenethyl ester (CAPE), a main active component of propolis and a flavonoid, is one of the natural products that has attracted attention in recent years. CAPE, which has many properties such as anti‐cancer, anti‐inflammatory, antioxidant, antibacterial and anti‐fungal, has shown many pharmacological potentials, including protective effects on multiple organs. Interestingly, molecular docking studies showed the possibility of binding of CAPE with replication enzyme. In addition, it was seen that in order to increase the binding security of the replication enzyme and CAPE, modifications can be made at three sites on the CAPE molecule, which leads to the possibility of the compound working more powerfully and usefully to prevent the proliferation of cancer cells and reduce its rate. Also, it was found that CAPE has an inhibitory effect against the main protease enzyme and may be effective in the treatment of SARS‐CoV‐2. This review covers in detail the importance of CAPE in alternative medicine, its pharmacological value, its potential as a cancer anti‐proliferative agent, its dual role in radioprotection and radiosensitization, and its use against coronavirus disease 2019 (COVID‐19).